2015
DOI: 10.1097/ta.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of a multinational “walking blood bank” in a combat zone

Abstract: Therapeutic study, level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We identified 17 studies reporting about patients with traumatic hemorrhage treated with at least 1 unit WB (without BCT comparison) including 10 retrospective cohort studies, 4 case series, and 3 prospective observational studies 12,14,58–72 . All studies are summarized in Supplementary Digital Content 13, http://links.lww.com/TA/D6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 17 studies reporting about patients with traumatic hemorrhage treated with at least 1 unit WB (without BCT comparison) including 10 retrospective cohort studies, 4 case series, and 3 prospective observational studies 12,14,58–72 . All studies are summarized in Supplementary Digital Content 13, http://links.lww.com/TA/D6.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 17 studies reporting about patients with traumatic hemorrhage treated with at least 1 unit WB (without BCT comparison) including 10 retrospective cohort studies, 4 case series, and 3 prospective observational studies. 12,14,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] All studies are summarized in Supplementary Digital Content 13, http://links.lww.com/TA/D6. In brief, included studies reported that WB transfusion is feasible in both military medicine, 62,68 and civilian medicine, 12,70,71 including in the prehospital setting.…”
Section: Wb Transfusion Without Bct Comparisonmentioning
confidence: 99%
“…As prehospital transfusion practices continue to advance across the globe, the face of resuscitation for patients in hemorrhagic shock also continues to evolve. 9,13 The recent addition of whole blood in trauma resuscitation algorithms has led to the potential for improved survival in civilians. For severely injured patients, earlier reversal of shock physiology has the potential benefit to improve both short-and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…8 Beyond the US Military, whole blood use has become a multinational practice with wartime collaboration and development of civilian whole programs around the world. 9 In civilian prehospital resuscitation, previous studies focused on the impact of prehospital plasma on patients in hemorrhagic shock secondary to trauma. 10 Few studies have specifically addressed the use of whole blood in the civilian prehospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Current FMHS guidelines also include on‐site collection of “warm” fresh whole blood from prescreened donors . In our series, this procedure was used in Role 2 MTFs for seven casualties, with blood collection being performed by colocated Role 1 teams.…”
Section: Discussionmentioning
confidence: 99%